Social characteristics of the noble lineage in the governorates of Iraq for the year 2021 - زهراء باسم محمد; أ.م.د. صباح وهب عبد الله (Journal of College of Education, 2023)
Social characteristics have an important role in population studies because they explain the changes taking place in the population in the community and the study of variance at the level of one governorate. The development of these characteristics depends on social, economic and political factors.